Synthesis and Characterization of α-Cellulose from Young Coconut Coir (Cocos nucifera L.) - Gracella Evangeline Sarumaha; Zainuddin Muchtar (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
Young coconut (Cocos nucifera L.) is a plant with a high cellulose content of 28%. Because of its high cellulose content, young coconut coir fiber has the potential to be synthesized into α-cellulose. The purpose of this research was to use FT-IR to characterize young coconut coir α-cellulose. This research method was use isolation of α-cellulose method (delignification, swelling, and bleaching). 75 grams of young coconut coir can produce 12,1015 grams of α-cellulose. Young coconut coir α-cellulose has a spectrum that is similar to commercial α-cellulose, according to the results of functional group analysis using FT-IR.